810 nm near-infrared light offers neuroprotection and improves locomotor activity in MPTP-treated mice. (March 2015) - Reinhart, Florian; Massri, Nabil El; Darlot, Fannie; Torres, Napoleon; Johnstone, Daniel M.; Chabrol, Claude; Costecalde, Thomas; Stone, Jonathan; Mitrofanis, John; Benabid, Alim-Louis; Moro, Cécile
Highlights: 810 nm near-infrared light offered neuroprotection in the MPTP-treated mice. 810 nm near-infrared light improved behaviour in MPTP-treated mice. 810 nm near-infrared light provided a similar degree of neuroprotection to 670 nm. 810 nm near-infrared light had a more striking behavioural effect on MPTP-treated mice than 670 nm. Abstract: We explored whether 810 nm near-infrared light (NIr) offered neuroprotection and/or improvement in locomotor activity in an acute 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-treated mouse model of Parkinson's disease. Mice received MPTP and 810 nm NIr treatments, or not, and were tested for locomotive activity in an open-field test. Thereafter, brains were aldehyde-fixed and processed for tyrosine hydroxylase immunohistochemistry. Our results showed that MPTP-treated mice that were irradiated with 810 nm NIr had both greater locomotor activity (∼40%) and number of dopaminergic cells (∼20%) than those that were not. In summary, 810 nm (as with 670 nm) NIr offered neuroprotection and improved locomotor activity in MPTP-treated mice.